2011
DOI: 10.2500/ar.2011.2.0005
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Fungal Concentration in the Homes of Allergic/Asthmatic Children in Delhi, India

Abstract: Allergy to fungi has been linked to a wide range of illnesses, including rhinitis and asthma. Therefore, exposure to fungi in home environment is an important factor for fungal allergy. The present study was aimed to investigate types of airborne fungi inside and outside the homes of asthmatic children and control subjects (nonasthmatic children). The dominant fungi were evaluated for their quantitative distribution and seasonal variation. The air samples were collected from indoors and immediate outdoors of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Our study showed that dominant fungi recovered from nasal cavity and bedrooms of healthy volunteers were Aspergillus, Penicillium, Yeast, Alternaria and Cladosporium; these findings are in agreement with the findings of several other researches (3,(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that dominant fungi recovered from nasal cavity and bedrooms of healthy volunteers were Aspergillus, Penicillium, Yeast, Alternaria and Cladosporium; these findings are in agreement with the findings of several other researches (3,(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 93%
“…Awad et al in Egypt reported that the most prevalent fungal organisms recovered in the air of urban and rural homes were Alternaria, Aspergillus, Cladosporium, Penicillium and Yeasts (24). Sharma et al in India showed that in control homes (non-asthmatic/ healthy volunteers), a similar spectrum of fungi was observed as in the homes of asthma patients, and different species of Aspergillus, Alternaria, Cladosporium, and Penicillium were the most prevalent fungi in homes of Delhi (16).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, morphologically, 78.65% of the isolates from both groups belonged to 4 genera: Aspergillus, Penicillium, Cladosporium and Alternaria fungi which are commonly considered allergenic; these findings are in agreement with the findings of several other researchers (12)(13)(14)(15)(16)(17)(18)(19). In the current study, fungi were isolated from 92% and 64% nasal cavity of healthy volunteers and patients with allergic rhinitis, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have investigated the isolation and frequency of allergen fungi in homes of healthy subjects and asthmatic/rhinitis patients (12)(13)(14)(15)(16)(17). The studies performed in different countries provide variable results of total fungal concentration and distribution of fungal species because it basically depends on media and sampling method used, season of the year, geographical location, and living conditions as well as fungal growth substrates in different countries (26).…”
Section: Discussionmentioning
confidence: 99%
“…Although extensive studies are lacking, several studies support the assumption that A. fumigatus is the more abundant pathogen in the environment [40,41]. In addition, A. fumigatus conidia are more efficiently dispersed in the environment due to their higher hydrophobicity [42].…”
Section: Discussionmentioning
confidence: 93%